PREVALENCE, INTENSITY AND RISK FACTORS OF SOIL TRANSMITTED HELMINTHS INFECTIONS AMONG ELEMENTARY SCHOOL STUDENTS IN NGIS VILLAGE, KARANGASEM DISTRICT, BALI - Arta Suryantari, Sang Ayu (Indonesian Journal of Tropical and Infectious Disease, 2019)
Soil Transmitted Helminths (STH) infections is one of health issues in Indonesia that has environment and social basis. It is classified as neglected disease. The Indonesian government already has eradication program, but it is not supported by evaluation and monitoring program. The purpose of this study is to determine the prevalence and relation of each risk factors related to STH infections in elementary school in Ngis village, Karangasem regency, Bali. The study was done by analytical description using cross sectional study. Samples were selected from population based on inclusion and exclusion criteria. Primary data about suspected risk factors were collected using questionnaire. Diagnosis was established using Kato-Katz modification method. Data was analyzed using chi-square with confidence interval 95% or p value â‰¤0.05 categorized as significant. 138 students enrolled in this study, the median age is 9 (6-13) years. The prevalence of STH infections is 10.1% with 78.6% is single infection of Trichuris trichiura and 21.4% mixed infections. The proportion of STH infections in males is higher than female but it is statistically insignificant. STH infections have significant relationship with some risk factors such as not washing hand after defecation, not washing hand after playing with soil, barefoot, not cutting nails and consuming anti-helminthic routinely. The highest risk factor of STH infections in Ngis village is not having available and proper latrine. (OR=33.9; 95%CI=5.749-199.769). The prevalence of STH infection is quite high with mild to moderate intensity and risk factors namely low hygiene and limited latrines. The implementation of monitoring and evaluation can be an effort to control risk factors and stop the STH transmission chain.